Perspektif Psikologi Sosial - Sugiyono Sugiyono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Environment is the most important and fundamental part of human life. Since birth man has been in a new environment and foreign to the man himself. This research leads to one main thing that is want to know the behavior change of new santri to old santri Pondok Pesantren Darussalam Village Blokagung District Tegalsari Banyuwangi Regency. To answer the existing problems the researcher uses qualitative approach method in doing research. In collecting data using interview data, participant observation and documentary. The supporting factors to know the change of santri behavior are 2 Intern (a) Natural incentives as social beings (b) Encouragement to meet the needs (c) Encouragement to develop themselves. (E) Motivation. From the research result, there are 2 factors, positive and negative, positive factor such as (1) performing congregational prayer at the beginning of time in the mosque (2) clean room or dormitory (3) nadzoman recall according to its level. The negative factor (1) sleep in the morning (2) lazy night prayer (3) slow praying congregation 5 time in the mosque.